The Influence of Brand Image and Customer Experience on Customer Loyalty Mediated by Customer Satisfaction - Robbani, Zidan Rizki; Alviyandi Agim Mulyadin; Aang Curatman; Rahmadi (Syntax Corporation, 2025)
This study aims to analyze the influence of brand image and customer experience on customer loyalty mediated by customer satisfaction at Papagesha Coffee Shop in Majalengka. A quantitative approach was used by involving 160 respondents aged 15–60 years. Data collection was conducted using a questionnaire based on the Likert scale, and analyzed using the PL-SEM method. As a result, brand image and customer experience have a positive and significant influence on customer satisfaction and loyalty. Customer satisfaction has proven to be a powerful mediator in strengthening the relationship between brand image and customer experience to customer loyalty. The findings also show that customer satisfaction has the most dominant influence in driving loyalty. It reinforces the importance of service improvement strategies, brand consistency, and meaningful experience creation to retain customers amid increasingly fierce competition in the coffee shop industry. The recommendations from this study emphasize the need for continuous innovation and holistic management of customer experience as the basis for strengthening long-term relationships between consumers and brands.